Feira de ciências e mostras : propostas para a alfabetização científica - Kato, Eneida Aparecida Jezur (2022)
This research is part of the Natural Sciences field, qualitative in its nature, characterized as Bibliographic Research, with the objective of identifying Scientific Literacy identifiers in works by students from public schools presented at XII MECTI - State Exhibition of Science and Technology and Innovation, carried out by the State Department of Science, Technology and Innovation (SECITECI) of the State of Mato Grosso, in partnership with CNPq in 2020. The evaluation was based on indicators suggested by Sasseron (2008), we were able to indicate the level of development of the Scientific Literacy process, so we made some adaptations to the reality of our students. Thirty-nine works were analyzed in the form of a banner; we consulted the Annals of the event and its regulation to verify if they met the established criteria. To evaluate the works, we have created categories for classification and analysis of the contents, such as keywords, theme, objective and description. The data showed that the participation of schools and students was small, the themes were not very specific, focused on broader issues of Science, only a few dealt with innovations in Science and Technology. Most students did not follow the steps of scientific methodology. They present difficulties regarding objectives, hypotheses, description of research stages and language. They demonstrate to be at the initial level of the Scientific Literacy process. This shows the urgent need to invest in science teaching with continuing teacher training aimed at teaching Science, Scientific Methodology and pedagogical practices. The education and the school systems should support and encourage the development of research projects, holding of Scientific Fairs and Exhibitions at school and student participation in scientific events outside of it.